What do we know about the labor share and the profit share? Part II: Empirical studies - Olivier Giovannoni (Levy Economics Institute of Bard College, 2014)
In this second part of our study we survey the rapidly expanding empirical literature on the determinants of the functional distribution of income. Three major strands emerge: technological change, international trade, and financialization. All contribute to the fluctuations of the labor share, and there is a significant amount of self-reinforcement among these factors. For the case of the United States, it seems that the factors listed above are by order of increasing importance. We conclude by noting that the falling US wage shares cointegrates with rising inequality and a rising top 1 percent income share. Thus, all measures of income distribution provide the same picture. Liberalization and financialization worsen economic inequality by raising top incomes, unless institutions are strongly redistributive. The labor share has also fallen, for structural reasons and for reasons related to economic policy. Such explanations are left to parts III and IV of our study, respectively. Part I investigated the theories of income distribution.
Keywords: D33; E24; E25; 330; Wage Share; Labor Share; Profit ShareTechnology; International Trade; Finance; Bargaining Power